Lake monster mysteries : investigating the world's most elusive creatures - Radford, Benjamin, 1970- (University Press of Kentucky, 2006)
For centuries, eyewitnesses around the world-from America to Africa, Argentina to Scotland-have reported sightings of dark, mysterious creatures in area lakes that surface briefly, only to quickly disappear. While the most famous lake monsters, those living in Loch Ness and Lake Champlain, have gained international notoriety, hundreds of lakes around the world are said to shelter these shadowy creatures. Lake Monster Mysteries is the first book to collectively approach these widespread mysteries from a scientific perspective. By using exhaustive research and results from firsthand investigati.